2020
DOI: 10.1042/bsr20193893
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: LncRNA EGOT regulates the proliferation and apoptosis of colorectal cancer by miR-33b-5p/CROT axis

Abstract: Accumulating researches have proved that long noncoding RNAs (lncRNAs) regulate a variety of cellular processes during cancer progression. However, the detailed function of most lncRNAs in colorectal cancer (CRC) remains mostly unknown. This study was aimed at exploring the specific role of lncRNA EGOT in CRC. Data from this study revealed that EGOT expression was obviously upregulated in CRC tissues and cell lines, and high EGOT expression indicated poor overall survival of CRC patients. Besides, functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Of note, Chen et al (2018) reported that IKZF1 overexpression promoted immune infiltration in several tumor types, and enhanced the efficacy of anti-PD1 and anti-CTLA4 treatment. Besides, non-coding RNAs in our study, including LINC00324 (Ni et al, 2019;Zhang M. et al, 2020), miR-9-5p (Ma et al, 2020;Wang et al, 2020), and miR-33b-5p (Huang G. et al, 2020;Ni et al, 2020), were also reported in literatures to be associated with the prognosis of various cancer types.…”
Section: Discussionsupporting
confidence: 73%
“…Of note, Chen et al (2018) reported that IKZF1 overexpression promoted immune infiltration in several tumor types, and enhanced the efficacy of anti-PD1 and anti-CTLA4 treatment. Besides, non-coding RNAs in our study, including LINC00324 (Ni et al, 2019;Zhang M. et al, 2020), miR-9-5p (Ma et al, 2020;Wang et al, 2020), and miR-33b-5p (Huang G. et al, 2020;Ni et al, 2020), were also reported in literatures to be associated with the prognosis of various cancer types.…”
Section: Discussionsupporting
confidence: 73%
“…Based on our bioinformatics prediction, and verified by dual-luciferase assay, we revealed that TP53TG1 serves as a competing endogenous (ceRNA) in its negative regulation of miR-33b in RB. MiR-33, specifically miR-33a and miR-33b, belongs to a family of highly conserved miRNA 34 , that are known tumor suppressors for cancers like HER2 positive breast carcinoma 35 , colorectal cancer 36 , and lung cancer 37 . Being a potential tumor suppressor, breast HER2 + tumor samples showed a marked downregulation of miR-33b, as opposed to normal breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Furthermore, it is found that EGOT can promote the apoptosis of CC through microRNA-33b-5p/CROT axis. 29 However, the predictive value of EGOT in clinical diagnosis of CC is still unclear. In this research, we first analyzed the expression of EGOT in CC.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the study of Ni et al, 29 this study was designed to analyze the diagnostic value of LncRNA EGOT in CC, and the ceRNA map was mapped by miR and its downstream mRNA which could bind to LncRNA EGOT . In addition, we also carried out a nude mouse experiment to verify the inhibitory effect of LncRNA EGOT on tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%